PENGARUH KEMUDAHAN AKSES DALAM PENGGUNAAN APLIKASI OJEK ONLINE DI KOTA PRABUMULIH - Yudi Tusri; Sri Suparni; Siska Alfiati; Rona Anggrainie (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2025)
This study aims to determine the effect of ease of access on the use of online motorcycle taxi applications in Prabumulih City. The method used in this study is a quantitative method with a descriptive approach, namely a method that aims to describe the relationship between variables based on data and analyzed statistically. The sampling technique was carried out by accidental sampling of 96 respondents. Data were collected through questionnaires and analyzed using SPSS version 26. The results of the study indicate that ease of access has a positive and significant effect on the use of online motorcycle taxi applications. The coefficient of determination value of 0.493 indicates that 49.3% of the variation in the use of online motorcycle taxi applications can be explained by this variable.